Nowe CuInS2 kropki kwantowe jako znaczniki fluorescencyjne w bioobrazowaniu: synteza i charakterystyka - Michalska, Martyna (My University, 2015)
Kropki kwantowe (ang. quantum dots, QDs) to półprzewodnikowe nanokryształy o wielkości od 2 do 10 nm, posiadające unikalne właściwości optyczne i elektryczne wynikające z kwantyzacji ruchu nośników ładunku w trzech kierunkach. Celem pracy była synteza wolnych od metali ciężkich kropek kwantowych jako potencjalnych sond fluorescencyjnych do bioobrazowania, ich charakterystyka fizykochemiczna, funkcjonalizacja ligandem specyficznym dla receptora (HER2) nowotworu piersi i ostatecznie weryfikacja właściwości aplikacyjnych otrzymanych sond w obrazowaniu in vitro komórek nowotworowych. Jako fotoaktywny rdzeń wybrano trójskładnikowy półprzewodnik CuInS2. Następnie otoczono go powłoką w postaci ZnS, aby poprawić właściwości optyczne rdzenia. W celu zdyspergowania kropek w wodzie, CuInS2/ZnS QDs posiadające hydrofobowe ligandy zmodyfikowano powierzchniowo poprzez otoczenie ich amfifilowym polimerem. Otrzymane nanokryształy sfunkcjonalizowano peptydem swoistym dla HER2 i ostatecznie wykazano ich skuteczność w obrazowaniu in vitro HER2-pozytywnego raka piersi.

Quantum dots (QDs) are size-quantized semiconductor nanocrystals that possess unique optical properties attributed to the quantum confinement effect. The aim of this study was to develop new heavy metal-free QD-based nanoprobes for potential applications in bioimaging. CuInS2 ternary nanocrystals as a core material are proposed. The QDs synthesis, phase transfer, characterization and band gap engineering were the general objectives. Moreover, QDs functionalization with a targeting ligand toward cancer cells was the aim of this work, in order to verify whether they could be useful as a fluorescent tool in cancer cells imaging. First, CuInS2 core QDs were synthesized via a non-injection approach, followed by a ZnS shell introduction. Subsequently, CuInS2/ZnS QDs were successfully transferred into water using an amphiphilic polymer. A HER2 receptor-binding peptide as a targeting ligand was anchored to the nanocrystals surface via diamine spacer. Finally, an imaging experiment was performed revealing that peptide-linked QDs can be a potential tool for HER2-pisitive cancer cells imaging.
Novel CuInS2 quantum dots as fluorescent probes for bioimaging: synthesis and characterization
Wydział Fizyki
Keywords: CuInS2 kropki kwantowe; CuInS2 quantum dots; modyfikacje powierzchni; surface modification; diagnostyka nowotworów; cancer diagnosis; HER2 receptor; HER2 targeting; obrazowanie molekularne; molecular imaging